NLP, Machine Learning Optimizing Machine Learning in Natural Language Processing to Analyze User Sentiment in the Tiktok Social Media Application: Optimizing Machine Learning in Natural Language Processing to Analyze User Sentiment in the Tiktok Social Media Application - Fahmi Setiawan; Izhar Fradila; Alwi Pernando; Supina Batubara (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to optimize the use of Machine Learning in Natural Language Processing (NLP) to analyze user sentiment in the social media application TikTok. The growth and development of the TikTok application among users, makes it important for users to understand users' views and feelings towards the content they consume by exploring various Machine Learning techniques that can be used to classify TikTok user sentiment based on text produced using NLP methods, it is hoped that this can provide useful insights. valuable in understanding TikTok users' responses and preferences to the content they encounter on the TikTok platform.